Coronary heart disease among adult population evacuated from the 30-km zone of the Chernobyl NPP (Descriptive epidemiologic research results). Observation period 1988-2012 - Olga A. Kapustynskaia (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2015)
The determination and analyses of the dynamics of the evacuated adults sickness rate of the coronary heart disease also including its particular types including of age at the time of the accident sex and from the moment of the accident. The materials of the Ukrainian public register of people who suffered from the Chernobyl accident (UPR) and the statistical data of the Ministry of Healthcare about the sickness of the Ukrainian population are used in the article. Subject of inquiry: adult population at the time of the accident avacuated from the 30-km Zone of the Chernobyl APP. Object of research - Coronary heart disease. The research was made on the coronary heart disease in whole and also due to nosological forms: angina pectoris; cardiac infarction; chronic coronary heart disease. Descriptive epidemiologic research was made for the period of 1988-2010 years. The cohort of adult avacuated population constituted 55022 people, 22056 men and 32966 women off them. For the comparison the statistic data about the sickness of adult population of Ukraine were used. In the article was also used the method of inner comparison, which allows to evaluate the credibility of the sickness rate figures difference for the periods of observation. The analisys is carried through following five periods (1988-1992 years, 1993-1997 years, 1998-2002 years, 2003-2008 years, 2009-2010 years). In accordance with the 24-years medical observation was determined that the coronary heart disease incidence of the adult evacuated population has significant differences due to age, sex and time. The increase in the coronary heart disease incidence regardless age at the moment of the accident is to be considered for the period of 12-22 years. The peak of the sickness for those, who were 40-60 at the time of the accident, was registered for the third period of observation, i. e. after 12-16 years from the moment of the accident at the Chernobyl NPP, for those, evacuated at the age of 18-39 - after 17-22 years and remains at the same level in the last period. 24 years later after the accident the rate of sickness of those, evacuated at the age 18-39, surpasses the figures of the first period four times and the second period - 3 times. In the age group of 40-60 years in the last period of observation the decrease is noted. High enough coronary heart disease incidence of those people, whose age at the time of accident was 40-60 at the first six years from the moment of the accident keeps attention, that, obviously, was caused by the influence of three main factors: "age", "screening-effect" and "psycho-social stress". For people evacuated at the age of 18-39 the proved difference in the sickness rate of men and women wasn't stated, whereas the figures of coronary heart disease for women of 40-60 years old are higher in comparison with men with an exception of the last stage of observation. What the particular forms of the coronary heart disease concerns the prevaluating of the cronical coronary heart disease is noted. For the people evacuated at the age of 18-39, was noted the higher frequency growth rate of angina pectoris and cardiac infarction in comparison to the people of age 40-60. In2009-2010 the sickness rate for these diseases for the people evacuated at the age of 40-60 was almost equal to the sickness rate of the first stages of observation. There is the hypothesis about the possible connection between frequency growth rate of coronary heart disease for the contingent of the sufferers with the exposure to radiation among those under observation and the impact of the complex of factors of nonradiation nature connected and not connected to the consequences of the Chernobyl APP accident, which is the task for the further analitical epidemiologic research.